Twenty years of the methadone treatment protocol in Ireland: reflections on the role of general practice - Ide Delargy; Des Crowley; Marie Claire Van Hout (BMC, 2019)
Abstract Background Opioid dependence, characterised by socio economic disadvantage and significant morbidity and mortality, remains a major public health problem in Ireland. Through the methadone treatment protocol (MTP), Irish general practice has been a leader in the introduction and expansion of Irish harm reduction services, including opioid substitution treatment (OST), needle and syringe programs (NSP) and naloxone provision. These services have been effective in engaging opiate users in treatment, reducing human deficiency virus (HIV) and hepatitis C virus (HCV) transmission and reducing-drug related morbidities. Challenges remain in relation to choice of substitution treatments, timely access to OST services, adequate coverage of NSP, naloxone provision and increasing drug-related deaths. Methods A narrative review was conducted and designed to present a broad perspective on the Irish MTP and to describe its history and development in terms of clinical care, stakeholder views and changing trends. Results Three themes emerged from the analysis; The History of the Methadone Treatment Protocol, Service User and Provider Views and Challenges and Developments. Despite the initial concern about methadone maintenance treatment (MMT) in Ireland, increased participation by Irish GPs in the treatment of opioid dependence is observed over the last two decades. There are now over 10,000 people on methadone treatment in Ireland, with 40% treated in general practice. The MTP provides structure, remuneration and guidance to GPs and is underpinned by training, ongoing education and a system of quality assurance provided by the Irish College of General Practice (ICGP). Challenges include the negative views of patients around how methadone services are delivered, the stigma associated with methadone treatment, the lack of choice around substitution medication, waiting lists for treatment in certain areas and rates of fatal overdose. Conclusion Twenty years of the MTP has been the mainstay of harm reduction services in Ireland. It has provided a network of specially trained GPs who provide methadone to over 10,000 patients across Ireland within a structured framework of training, quality assurance and remuneration. With the ongoing commitment of Irish specialists in the field of addiction medicine, further improvements to support and treat patients can be made.